APLIKASI REGRESI SPASIAL UNTUK MENGANALISIS PENGARUH INDIKATOR PENDIDIKAN TERHADAP TINGKAT PENGANGGURAN TERBUKA DI JAWA TENGAH TAHUN 2018 - Rizqi, Ulul Azmi Afrizal (EP FEB UNS, 2019)
Unemployment still becomes one of social important problems in Indonesia that needs more attention, including in Central Java. One factor that affects the unemployment rate is educa-tion. Education is a gateway for people to improve their living standards through the worklife. Moreover, education will improve the quality of human resources themselves. This study tries to analyze unemployment in the context of spatial distribution to understand wheter or not there is spatial pattern of unemployment in Central Java. Descriptive analysis results indicate that there is a regional grouping of high open unemployment rates in Central Java, which is located in the western part of the province. The modeling results show that the Spatial Auto-regressive Model is appropriate to illustrate the effect of the independent relationship on the dependent variable. The model estimation results conclude that people (in the percentage of population) who have never / not yet attended school have positive effect on the open unem-ployment rates. While people (in percentage) who cannot read and write and the literacy rate of poor people aged 15-55 years have negative effect on the open unemployment rates. The results of this study can be a reference for the government in focusing its main policies on education and employment in Central Java.Keywords: education, spatial autoregressive model, unemploymenJEL Classification: C21, E24, I25